Learning Technology and Society in The Social Sciences - Euis Puspitasari (Ilmu Inovasi Nusantara, 2022)
The development of technology is very rapid. The institution of education cannot be separated from the use of technology. The use of technological applications in learning systems has become commonplace in this digital era. However, the use of technology in learning must be more selective which can have a positive impact on students. Learning is a process to obtain changes that are carried out consciously, actively, dynamically, systematically, continuously, integrative, and have clear goals. Learning is an activity in which there is a process of teaching, guiding, training, and giving an example. The research objectives of this research are; a) to find out learning using technology, b) to find out the community applies social science, and c) to know the community uses technology and social science. The research method used in research is library research. In this study, researchers used sources in the form of books, journals, articles, or reviews related to technological literacy. The results showed that institutions of education have accepted and many use technology as a support for the learning process. Then the second is that people who apply social science can develop an emotional, intellectual, and social culture that can teach students to have a way of thinking critically and behavior responsibility in a social society. In the end, science and technology have positive and negative impacts. The user of technology, society, or students must be more selective in the use of technology